2018
DOI: 10.1002/pits.22131
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles predict career readiness in early college high‐school students

Abstract: This study examined leadership style as a predictor of career readiness among a sample of (N = 281) students from two early college high schools from the Rio Grande Valley in South Texas. Participants included 165 females and 116 males ranging from 14 to 19 years of age and 96.8% identified as Hispanic. Participants provided demographic information and reported their own leadership style using the Multifactor Leadership Questionnaire (MLQ 5x) as well as their career readiness using the Employability Skills Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Leadership styles can have a positive impact on the development and use of organizational learning and commitment (Ebrahim and Yahaya, 2016), job and meeting JMD 40,1 satisfaction (Abdelhafiz et al, 2016), organization subordinates' performance (Kwanya and Stilwell, 2018;Nazarian et al, 2017;Sethibe, 2017), followers' innovative behaviour (Ahmed et al, 2018;Gong et al, 2018;Hansen and Pihl-Thingvad, 2019), work engagement and commitment (Ribeiro et al, 2018), risk-taking, decision-making participation and empowerment (Huertas-Valdivia et al, 2019), career readiness (Villarreal et al, 2018), positive working environment (Mills et al, 2018), total quality management practices (Kumar and Sharma, 2018;Soliman, 2018) and building followers' trust (Yasir et al, 2016).…”
Section: Leadership Stylesmentioning
confidence: 99%
See 2 more Smart Citations
“…Leadership styles can have a positive impact on the development and use of organizational learning and commitment (Ebrahim and Yahaya, 2016), job and meeting JMD 40,1 satisfaction (Abdelhafiz et al, 2016), organization subordinates' performance (Kwanya and Stilwell, 2018;Nazarian et al, 2017;Sethibe, 2017), followers' innovative behaviour (Ahmed et al, 2018;Gong et al, 2018;Hansen and Pihl-Thingvad, 2019), work engagement and commitment (Ribeiro et al, 2018), risk-taking, decision-making participation and empowerment (Huertas-Valdivia et al, 2019), career readiness (Villarreal et al, 2018), positive working environment (Mills et al, 2018), total quality management practices (Kumar and Sharma, 2018;Soliman, 2018) and building followers' trust (Yasir et al, 2016).…”
Section: Leadership Stylesmentioning
confidence: 99%
“…We searched the literature for the most used comprehensive and representative measurements for leadership styles. We found that the most prominent and used measurement tool is the Multifactor leadership Questionnaire (MLQ) (G€ unzel-Jensen et al, 2018;Mills et al, 2018;Vignoli et al, 2018;Villarreal et al, 2018;Zhang et al, 2018) with 45 questions using a 5-point Likert scale from 0 (not at all to 5 (always).…”
Section: Leadership Styles Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Various leadership programs and modules were developed in order for the students to improve their leadership skill [6]. However, several scholars have argued that leadership development should became a priority to build up the strong leadership characteristics, especially at young age [7][8][9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The idea of student leadership in the 21 st century has risen (Adams & Velarde, 2018), the call for student leadership gaining in momentum, as various enhanced leadership models and trends are developed for students Tie, 2012). Scholars argue that students' leadership development should be a priority to assist students to form a strong leadership identity at an early stage (Adams, Kamarudin, & Tan, 2018;Amirianzadeh, 2012;Keselman et al, 2015;Simonsen et al, 2014;Villarreal et al, 2018).…”
Section: Student Leadership and Development: A Panoramic View Of Trenmentioning
confidence: 99%